Penunjuk Kualiti Hidup Di Taman Perumahan Penduduk Di Bandar Baru Bangi, Selangor, Malaysia - Shafii, Haryati; Md. Jahi, Jamaluddin; Latiff, A. (Journal of Techno-Social, 2009)
Residential comfort is an important component in determining the overall society quality of life. This study identifies several aspects that contribute to a good quality of life, focusing on residential location, as well as internal and external thermal discomfort.The evaluation of thermal comfort with facilities and accessibility to facilities. The study area is Section 1 and 2, Bandar Baru Bangi, Selangor. A questioner survey was conducted on 207 from Section 1 and 117 from Section 2 to evaluate their thermal comfort at home and their perception of residence in relation to the environment. The respondent were selected from different dwelling types-bungalows, double-storey, and single storey linked units, apartment and flats. Temperature measurements were carried out from fout times daily, in the morning, evening, afternoon and night, for both the inside and out sideand outside of the 28 selected places of residence. The significance of correlations is determined through the use of chi square statistics. The study recorded interior temperatures between 23 °C and 31°C, and external temperatures between 25 °C to 23 °C. The study also identified high access to economic, social, transport and infrastructural facilities, available at a distance less than a kilometer from place of residence, for all study areas. Resident thus, enjoy good quality of life in relation to the aspects mentioned. This paper concludes with suggestion for future housing development to give higher consideration for housing that contributes to a higher quality of life through internal and comfort and external linkages to accessible amenities.